Evaluation of curcumin-loaded chitosan nanoparticles for wound healing activity - Smita Kumbhar; Rupali Khairate; Manish Bhatia; Prafulla Choudhari; Vinod Gaikwad (International Association of Physical Chemists (IAPC), 2023)
Background and purpose: Wound healing is a biological process that can be difficult to manage clinically. In skin wound healing, the interaction of many cells, growth factors, and cytokines reveals an outstanding biological function mechanism. Wound healing that occurs naturally restores tissue integrity, however, it is usually restricted to wound repair. Curcumin synthesised in a chitosan matrix can be used to heal skin sores. Experimental approach: The ionotropic gelation procedure required crosslinking chitosan with a tripolyphosphate (TPP) crosslinker to generate curcumin nanoparticles encapsulated in chitosan. Key results: The nanoparticles were between 200 and 400 nm in size, with a strong positive surface charge and good entrapment efficacy, according to SEM and TEM investigations. Curcumin and chitosan compatibility was investigated using FTIR spectroscopy. All batches showed consistent drug release, with the F5 batch having the highest curcumin release, at 75% after 16 hours. On L929 cells, scratch assays were utilised to assess wound healing. Wound closure with widths of 59 and 65 mm with curcumin and 45 and 78 mm with curcumin-loaded chitosan nanoparticles was seen after 24 and 48 hours of examination. Conclusions: According to the findings, prepared curcumin chitosan nanoparticles are beneficial in healing skin damage.